Enantiomorphy through the looking glass: literacy effects on mirror-image discrimination - Régine Kolinsky (2011)
To examine whether enantiomorphy (i.e., the ability to discriminate lateral mirror images) is influenced by the acquisition of a written system that incorporates mirrored letters (e.g., b and d), unschooled illiterate adults were compared with people reading the Latin alphabet, namely, both schooled literate adults and unschooled adults alphabetized in adulthood. In various sorting and same different comparison tasks with nonlinguistic materials, illiterate participants displayed some sensitivity to enantiomorphic contrasts but performed far worse than all the other participant groups when the task required paying attention to such contrasts. The difficulties of illiterate participants were more severe with enantiomorphs than with rotations in the plane or shape contrasts. Learning a written system that incorporates enantiomorphic letters thus pushes the beginning reader to break the mirror invariance characteristic of the visual system, and this process generalizes beyond the realm of symbolic characters.